The Lab-I cognitive empowerment: A new multifactorial training for older adults - Vranić, Andrea; Borella, Erika (2012)
The aim of the present study is to assess the efficacy of a multifactorial training (Lab-I cognitive empowerment) in which not only strategies but also motivational factors are trained. The sample is composed of 60 elderly participants (M=72.4) divided in 2 groups: experimental and control. Participants in the experimental group underwent 10-sessions in which they were taught strategies and memory functioning. Also, the importance of beliefs and efficacy of one’s own memory abilities was presented and discussed. Moreover, homework was assigned. The active control group underwent a 10-sessions program on different psychological topics. Short term, as well as maintenance effects (follow-up at 7 months), were examined on the measures of working memory, verbal long term memory, and fluid intelligence, as well as on the measures of emotional and non-cognitive factors (loneliness, psychological needs satisfaction, optimism-pessimism). Results showed that only the experimental group showed benefits in performance on all of the tasks used. Moreover, regression analyses of the post-test and follow-up results suggested that the benefit due to the training in the trained group could be partially accounted for by the benefit in emotional and non-cognitive factors.
Projekt MZOS
ENG